Coastal zones solutions for the 21st century - Baztan, Juan; Chouinard, Omer; Jorgensen, Bethany 1986-; Tett, Paul; Vanderlinden, Jean-Paul; Vasseur, Liette 1963- (Elsevier, 2015)
Coastal Zones: Solutions for the 21st Century bridges the gap between national and international efforts and the local needs for actions in communities where coastal zone challenges are faced daily. The solution-oriented approach covers issues of coastal zone management as well as responses to natural disasters. This work provides ideas on how to face the challenges, develop solutions, and localize management of common-pool resources. Coastal Zones targets academic stakeholders and coastal stakeholders who have local knowledge and experience but need a theoretical framework and a greater range of skills to make use of this experience.--Provided by publisher.